2015
DOI: 10.2340/16501977-1967
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue during and after cardiac rehabilitation

Abstract: Fatigue decreased during and after cardiac rehabilitation. However, the prevalence of severely fatigued patients remained high after cardiac rehabilitation. Fatigue should be identified at an early stage in order to provide additional programmes aiming to reduce severe fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…Preliminary studies suggested feasibility of a rehabilitation program after a VTE episode [ 23 ]. Whether such programs have the potential to decrease fatigue, as is the case in patients with coronary artery disease, need to be studied prospectively [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies suggested feasibility of a rehabilitation program after a VTE episode [ 23 ]. Whether such programs have the potential to decrease fatigue, as is the case in patients with coronary artery disease, need to be studied prospectively [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our population-based study was conducted in a rehabilitation centre, where subjects with CHF underwent a comprehensive intervention, based on a thorough patient assessment followed by patient-tailored therapies, which in clude, but are not limited to, exercise training, education, and behaviour changes. However, exercise remains the cornerstone of a rehabilitation programme for patients with heart disease (28)(29)(30)(31)(32). The results of the current study showed an exceptionally high prevalence of DISH among patients with CHF undergoing a programme of in-hospital rehabilitation, particularly in obese and older individuals.…”
Section: Discussionmentioning
confidence: 55%
“…8,9 To date, cardiac rehabilitation results for these outcomes have been suboptimal in patients with acute coronary syndrome. 8,10,11…”
Section: Introductionmentioning
confidence: 99%